QUESTIONS USED BY ENGLISH TEACHER IN TEACHING READING COMPREHENSION TO GRADE X AT SMAN 1 MUARA - Suryani G Siregar; Berlin Sibarani; Syamsul Bahri (Universitas Negeri Medan, 2020)
This research focused on the types of questions used by teacher and the reason for using the questions. It was a qualitative research design. The subject of this study was an English teacher of the tenth grade students of SMA Negeri 1 Muara. The data were collected by observing, video recording, and interview. The result showed that the teacher only used 4 out of 5 types of questions, they were question of literal, question of reorganization, question of inference, and question of personal response. It was also found that there were other types of questions which categorized as students’ knowledge, vocabulary, and students’ experiences. Out of the 4 types of question, the type of questions frequently used was question of literal. Followed by question of reorganization came as the second, and the least used by the teacher was question of personal response. The reasons for using the types of questions were to measure students’ comprehension and to facilitate students towards comprehension. Key words: teaching reading comprehension, types of questions